PENGARUH PENERAPAN MODEL PBL TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI “NORMA” KELAS V SEKOLAH DASAR - Widiyastuti, Indry; Rondli, Wawan Shokib; Ismaya, Erik Aditia (INOPENDAS: Jurnal Ilmiah Kependidikan, 2024)
It was found that there is a problem with the lack of innovative teaching models used by teachers. The purpose of this study is to examine the influence of the implementation of the Problem-Based Learning (PBL) model on students' learning outcomes in the subject of Pancasila Education, specifically on the "Norms" material for Grade V of elementary school. The population and sample of this study are all Grade V students of SDN 3 Jekulo. The method used in this study is a quantitative experiment with a one-group pretest-posttest design. Data analysis in this study used the Paired Sample T-Test. The results of the hypothesis test using the paired sample t-test showed that the Sig. (2-tailed) value was 0.000 0.05. Therefore, H0 is rejected and Ha is accepted. This implies that there is an influence of the PBL model on students' learning outcomes in the subject of Pancasila Education, specifically on the "Norms" material for Grade V of elementary school.